The extent to which the second intermediate grade math book includes active learning skills (Journal of the College of Basic Education, 2023)
The aim of the current research is to know the extent to which the second intermediate grade mathematics book includes active learning skills:To achieve the goal of the research, the researchers adopted the descriptive analytical approach, as the research sample was represented by the content of the mathematics book, which is scheduled for students of the second intermediate grade for the academic year (2021-2022) in Iraqi schools. The researchers prepared a content analysis card according to the active learning skills, and its validity was confirmed after presenting it to a group of specialized arbitrators, and it obtained an agreement rate of more than (80%) of the arbitrators' opinions.The analysis card consisted of the main and sub-skills of active learning, with (8) main skills, and (22) sub-skills.The target mathematics book was analyzed in its first and second parts according to the main and subsidiary active learning skills. Through re-analysis after a specified period of time), and the second method was the use of other analysts.A result was reached that included the second intermediate grade math book on active learning skills (the main and most of the sub-skills of them) in varying proportions. As the main skills got close percentages in the mathematics book of the second intermediate grade, where (Organization Skill) got the first rank with an average percentage that included (27.1%), and a low degree of availability, and (The skill of collecting information) got the eighth rank with an average percentage that included (3.6%(, and the degree of availability is very weak.According to these results, a number of recommendations were made, including:The necessity of including active learning skills within the second intermediate grade book in a balanced manner that complements each other .He made a number of suggestions, including:- Conducting similar studies in different study courses.